Prevention of Anemia in Adolescents Through Nutrition Education And Iron Supplementation in Cihideung Village in 2025 - Mufti, Iga Retia; Farida, Mila Latipah (Jurnal Pengabdian Masyarakat, 2025)
Purpose: This study aimed to prevent anemia among adolescents by increasing their knowledge and improving hemoglobin levels through nutrition education and iron supplementation. Anemia is a significant public health problem among adolescents, especially girls, caused by increased iron requirements, unbalanced dietary patterns, and limited nutritional awareness. Method: A quasi-experimental design with a pre-test and post-test without a control group was employed. The study involved 70 adolescents aged 13–18 years in Cihideung Village, Bandung Barat Regency. Participants attended interactive nutrition education sessions and received iron supplementation for 15 days. Data were collected using knowledge questionnaires and hemoglobin measurements and analyzed with a paired t-test. Practical Applications: The findings can be applied to develop community-based interventions for anemia prevention among adolescents. Implementing similar programs in schools and youth organizations may enhance awareness, encourage healthy eating behaviors, and reduce anemia prevalence. Conclusion: The intervention significantly increased adolescents’ knowledge and improved hemoglobin levels, reducing anemia prevalence from 34.3% to 18.6%. Combining education with supplementation is an effective strategy for preventing anemia in adolescents.